The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1093/hmg/8.13.2479
|View full text |Cite
|
Sign up to set email alerts
|

The Mutational Spectrum of the Sonic Hedgehog Gene in Holoprosencephaly: SHH Mutations Cause a Significant Proportion of Autosomal Dominant Holoprosencephaly

Abstract: Holoprosencephaly (HPE) is a common developmental anomaly of the human forebrain and midface where the cerebral hemispheres fail to separate into distinct left and right halves. We have previously reported haploinsufficiency for Sonic Hedgehog ( SHH ) as a cause for HPE. We have now performed mutational analysis of the complete coding region and intron-exon junctions of the SHH gene in 344 unrelated affected individuals. Herein, we describe 13 additional unrelated affected individuals with SHH mutations, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
280
2
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(298 citation statements)
references
References 34 publications
12
280
2
4
Order By: Relevance
“…The three of these five that clearly cosegregate with an HPE phenotype (G31R, W117G, and W117R) showed the strongest functional impairments (see below). A fourth, D88V, although not associated with HPE in the heterozygous mother of the proband, shows a pattern of cosegregation in second-degree relatives that could be consistent with incomplete penetrance of the mutation (19). The fifth alteration, N115K, is not associated with HPE in the mother of the proband, and no other evidence of cosegregation with phenotype exists.…”
Section: Weak Shh Mutations Show Poor Hpe Cosegregation In Pedigreementioning
confidence: 80%
“…The three of these five that clearly cosegregate with an HPE phenotype (G31R, W117G, and W117R) showed the strongest functional impairments (see below). A fourth, D88V, although not associated with HPE in the heterozygous mother of the proband, shows a pattern of cosegregation in second-degree relatives that could be consistent with incomplete penetrance of the mutation (19). The fifth alteration, N115K, is not associated with HPE in the mother of the proband, and no other evidence of cosegregation with phenotype exists.…”
Section: Weak Shh Mutations Show Poor Hpe Cosegregation In Pedigreementioning
confidence: 80%
“…Furthermore, such ophthalmologic signs have been described, associated with SHH mutations. 11 The variable expression of the SIX3 mutations might be explained by environmental factors and/or potential modifying genes. This hypothesis was supported by Nanni et al 11 who reported three patients with both an SHH mutation and abnormalities in ZIC2 or TGIF genes.…”
Section: Discussionmentioning
confidence: 99%
“…20,[22][23][24][25][26] Several syndromic genes are involved in developing other organs in addition to the eye, including CHD7, the gene for CHARGE syndrome 27,28 and PTCH, the gene for Gorlin syndrome. 29 There is a complex interplay between the different eye development gene pathways, which allows their expression to be finely regulated 5,27,30 and begins to explain why there is such an overlap of the phenotypes associated with mutations of each gene. For a more complete list of conditions associated with coloboma, the reader is referred to the reviews by Gregory-Evans et al and Chang et al 5,6 …”
Section: Aetiology and Geneticsmentioning
confidence: 99%